Genetic Basis of Carbamazepine Hypersensitivity - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2001)
The genetic basis of carbamazepine hypersensitivity was investigated in 60 affected patients (37 with mild rashes and 23 severe reactions) and 63 control non-sensitive subjects taking carbamazepine and treated at the University of Liverpool, UK.